I am required to find $\lim\limits_{x \to 0^+} \frac{xe^x}{e^x-1}$.

My attempt:

$\lim\limits_{x \to 0^+} \frac{xe^x}{e^x-1}$ = $\lim\limits_{x \to 0^+} e^x$ $\cdot$ $\lim\limits_{x \to 0^+} \frac{x}{e^x-1}$

$=1\cdot\lim\limits_{x \to 0^+} \frac{x}{e^x-1}$

$=\lim\limits_{x \to 0^+} e^{-x}$ (L'Hopital's Rule)

$= 1$ (which is the correct answer)

My question is: Why am I not able to apply the rule to the equation right from the beginning [since substituting $0$ we get $\frac{0}{0}$]?

$\lim\limits_{x \to 0^+} \frac{xe^x}{e^x-1}$

$=\lim\limits_{x \to 0^+} \frac{xe^x}{e^x}$

$=\lim\limits_{x \to 0^+}x$

$=0$ (wrong)

  • 4
    $\begingroup$ It is applicable, you're just computing the derivative wrong. $$(xe^x)^\prime = xe^x + e^x.$$ $\endgroup$ – Philip Hoskins Feb 14 '16 at 7:13
  • $\begingroup$ But why use L'Hopital's rule? $\endgroup$ – gniourf_gniourf Feb 14 '16 at 7:32

If you want to apply L'Hospital's rule right from the beginning, you may write $$ \begin{align} \lim\limits_{x \to 0^+}\frac{xe^x}{e^x-1}&=\lim\limits_{x \to 0^+}\frac{e^x+xe^x}{e^x}=\frac{1+0}1=1 \end{align} $$ since $$ (xe^x)'=e^x+xe^x. $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.